Global assessment of historical, current and forecast ocean energy infrastructure: Implications for marine space planning, sustainable design and end-of-engineered-life management. (February 2022) - Gourvenec, Susan; Sturt, Fraser; Reid, Emily; Trigos, Federico
Abstract: Thousands of structures are currently installed in our oceans to help meet our global energy needs. This number is set to increase with the transition to renewable energy, due to lower energy yield per structure, growing energy demand and greater and more diverse use of ocean space (e.g. for food, industrial or scientific activity). A clear and comprehensive picture of the spatial and temporal distribution of ocean energy assets is crucial to inform marine spatial planning, sustainable design of ocean infrastructure and end-of-engineered-life management, to prevent an exponentially increasing asset base becoming an economic and environmental burden. Here we define the spatial and temporal dimensions of the challenge that lies before us through creation of a comprehensive global dataset of past, current and forecast ocean energy infrastructure and offshore energy resources, both hydrocarbon and wind, for the period 1960–2040. The data is collected together for the first time and made available in the public domain through an interactive online map. The resulting oceanscape provides insight into the type, quantity, density and geographic centres of the accumulating asset base, which in turn enables informed consideration of how marine space alongside design and end-of-engineered-life of ocean infrastructure can be managed responsibly and sustainably. Highlights: Quantifies spatio-temporal distribution of offshore energy infrastructure globally 1960–2040. Online interactive map of evolution of offshore energy infrastructure 1960–2040 https://www.arcgis.com/apps/mapviewer/index.html?webmap=9205cfceff1744609cffbbdc315b0408 animation for illustration also available https://youtu.be/QbyYu5gh_3g . Evidence base to develop strategies to address critical marine spatial planning questions. Inter-disciplinary considerations for sustainable transition to ocean renewables.